Aplicación del modelo Usle para estimar cuantitativamente la erosión hídrica en la microcuenca del río Chibunga - Llamatumbi Paillacho, Evelyn Thalia (2021)
This study establishes the evaluation of soil water erosion in the Chibunga river micro-basin, with an area of 43,951 ha, located to the northwest of the Chimborazo province, belonging to the Chambo river sub-basin, by analyzing the factors that correspond to the USLE Universal Soil Loss Equation, managing to identify variables such as erosivity (R), erodibility (K), length and degree of slope (LS), vegetation cover and land use (C), soil conservation practices (P) and as a final result the soil loss factor (A). The variables used were: precipitation in the period (2000-2013); Soil textural structure: sand, silt, clay, and organic matter obtained from FAO-2007; the digital elevation model (DEM) with a resolution of 30 m2; the vegetation cover generated through the supervised classification, using orthophotos with resolution (1.19 m2) SAS PLANET-2020, processed in a geographic information systems software. The result of the USLE model's application determined that the Chibunga river micro-basin presents a degree of erosion due to water action, predominantly the light and moderate categories, which represents 30.47% and 46.17%, respectively, for the study area. The inputs such as geographic databases, geographic layers, and thematic maps generated will be useful for the actors in charge of land management by implementing acceptable agricultural practices, guaranteeing the sustainable management of the edaphic resource.